Pengaruh Equivalent Rate, Profitabilitas, dan Jumlah Kantor Terhadap Dana Pihak Ketiga BPRS di Indonesia (Periode Tahun 2013-2015) - Almira Ulfa Nugraheni; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to determine the effect equivalent rate, profitability and the number of offices to Third Party Funds of Sharia Rural Banks in Indonesia in 2013 until 2015. The research method used is a quantitative approach. The dependent variable in this study is the Third Party Funds, as well as the independent variable in this study is equivalent rate, the rate of profit andthe number of offices. Sample used is a saturated sampling and used multiple linear regression as analytical technique.Research results shows that the confidence level is 95%, equivalent rate, profitability, and the number of office have a significant effect on the magnitude of the amount of third party funds Sharia Rural Banks in Indonesia with 81.1% integration level. The partially, only the rate ofprofit and the number of office that significantly influence the large number of Sharia Rural banks in Indonesia.